The Springfield Gas Machine : Illuminating Industry and Leisure, 1860s-1920s. - Linebaugh, Donald W. (University of Tennessee Press, 2012)
Developed just after the close of the Civil War, the Springfield Gas Machine was a unique commercial and domestic gas lighting system marketed for use in homes and businesses outside of a city's gas works. The self-contained unit was perfectly suited to accommodate an expanding rural and suburban U.S. landscape as middle- and upper-class American families were looking to find simplicity in the countryside without losing any modern comforts of the city. Industries, too, were looking for a means to operate more efficiently and implement longer work hours for various production operations.